Age-specific mapping of QTLs associated with cold tolerance for seedling weight in rice (Oryza sativa L.) - YANG Yong-xia; P. K. Pathak; ZHU Jun (浙江大学学报. 农业与生命科学版)
A doubled haploid (DH) population derived from a across between a japonica male parent Azucena and a indica female parents IR64, was used for detecting QTLs related to seedling weight under 3-leaf cold treatment situation at five measuring stages, with additive, epistasis and their QE effects by unconditional and conditional mapping methods. The results showed that the numbers, the magnitude of the effects and the operation manner of the QTLs affecting seedling weight were different at different measuring stages. Of the 17 QTLs controlling seedling weight detected by unconditional mapping, 14 QTLs were found with significant additive × treatment interaction effects which determined the differential response of the seedling weight to environmental variation. Conditional QTL analysis indicated that the gene expressions were quite active at the intervals from 23th day to 30th day (a week after cold treatment) for the QTLs with various genetic effects, and the intervals from 16th day to 37th day (within three weeks from cold treatment starting) for the QTLs with additive × treatment interaction effects. In the study, with two mapping methods, there were 25 pairs of QTLs involved in epistasis for seedling weight, and most interactions were detected from 23th day to 30th day. Several important features of epistasis were also revealed.